2014
DOI: 10.1371/journal.pone.0084846
|View full text |Cite
|
Sign up to set email alerts
|

Similar Mechanisms Underlie the Detection of Horizontal and Vertical Disparity Corrugations

Abstract: Our aim was to compare sensitivity for horizontal and vertical disparity corrugations and to resolve whether these stimuli are processed by similar or radically different underlying mechanisms. We measure global disparity sensitivity as a function of carrier spatial frequency for equi-detectable carriers and found a similar optimal carrier relationship for vertical and horizontal stimuli. Sensitivity as a function of corrugation spatial frequency for stimuli of comparable spatial summation and composed of opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…It is generally accepted that our visual system processes disparity PLOS COMPUTATIONAL BIOLOGY along at least two [7][8][9][10][11] or more [12] channels that are selective for depth changes at different disparity spatial scales. These disparity spatial scales in turn may rely on distinct sets of luminance spatial channels [13][14][15][16] (as well as second-order channels [49][50][51]). A key insight provided by our work is that depth-selective channels emerge directly from the log-polar, retinocortical transform, since log-polar spatial sampling acts as a "sliding" multi-scale analysis, i.e.…”
Section: Plos Computational Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that our visual system processes disparity PLOS COMPUTATIONAL BIOLOGY along at least two [7][8][9][10][11] or more [12] channels that are selective for depth changes at different disparity spatial scales. These disparity spatial scales in turn may rely on distinct sets of luminance spatial channels [13][14][15][16] (as well as second-order channels [49][50][51]). A key insight provided by our work is that depth-selective channels emerge directly from the log-polar, retinocortical transform, since log-polar spatial sampling acts as a "sliding" multi-scale analysis, i.e.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…It has been proposed that the visual system may process disparity at different disparity spatial scales along separate channels [5], analogous to the channels selective for luminance differences at different luminance spatial frequencies [6]. Using a variety of paradigms to investigate both absolute and relative disparity processing, several authors have provided evidence for at least two [7][8][9][10][11] or more [12] disparity spatial channels for disparity processing, which in turn may rely on distinct sets of luminance spatial channels [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Witz and Hess, 12 using spatially band-pass noise rather than random dots, also concluded that vertical and horizontal stereo corrugations are detected by multiple disparity channels. 13 Thus, the single versus multiple disparity channel hypothesis for explaining the stereoscopic anisotropy cannot be sustained.…”
mentioning
confidence: 99%
“…The pattern of human disparity sensitivity that we observe is well captured by our 136 biologically-motivated model of disparity processing that critically incorporates the 137 log-polar retino-cortical transformation. It is generally accepted that our visual system 138 processes disparity along at least two [2,[4][5][6][7][8][9][10] or more [11][12][13] channels that are 139 selective for depth changes at different spatial scales. A key insight provided by our 140 work is that depth-selective channels emerge directly from the log-polar, retino-cortical 141 transform, since log-polar spatial sampling acts as an "horizontal" multi-scale analysis, 142 i.e.…”
mentioning
confidence: 99%
“…• The algorithm presented in [42] did not contain neural noise, which is instead 521 present in the human visual system [28] and was thus incorporated into the 522 current model 523 • In [42] a multi-scale approach was adopted with 11 sub-octave scales in order to 524 recover a large range of disparities (common in computer vision) by using Gabor 525 filters with peak frequency of 0.26 cycles/pixel. In the current model, only 2 scales 526 were employed, since several authors have proposed two spatial frequency channels 527 for disparity processing in humans [4][5][6][7][8][9][10]…”
mentioning
confidence: 99%